2012
DOI: 10.1145/2237796.2237805
|View full text |Cite
|
Sign up to set email alerts
|

Analytical models for trust based routing protocols in wireless ad hoc networks

Abstract: In Wireless Ad Hoc Network environment, there are three ways to understand a routing protocol: (i) monitoring, (ii) simulation and (iii) modeling. In this paper, the different trust based secure routing protocols used in wireless ad hoc networks are analyzed, modeled and described by incorporating process flow diagrams. These process flow diagrams represent stepwise work flow activities and actions. It shows the overall flow of control of a process, program or a protocol. This paper focuses on the security asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Secured Trust-aware Routing Protocol for Low-Power and Lossy Networks (SecTrust-RPL) in the IoT determines and detaches routing attacks by offering improved network performance (Airehrour, et al, 2019). Secure routing protocols, like Expected Forwarded Counter (EFW) (Paris, et al, 2013), Semi-Distributed Reputationbased Intrusion Detection System (S-D RepIDS) (Trivedi, et al, 2010), Trusted based routing using Dominating Set Approach (TRDSA) (Kukreja & Reddy, 2012), Secure Resilient Reputation-based Routing (SR3) (Altisen, et al, 2013), reputation-based Framework for Sensor Networks (RFSN) (Ganeriwal, et al, 2008), and Ad Hoc On-Demand Distance Vector Reputation Extension (AODV) (Over MANET, 2012)are illustrated. Secure Resilient Reputation-based Routing (SR3), Expected Forwarded Counter (EFW), and Trusted based routing using Dominating Set Approach (TRDSA) use reputation methods for core deductive components (Hatzivasilis, et al, 2017).…”
Section: Chaotic Whale Crow Optimization Algorithm For Secure Routing...mentioning
confidence: 99%
“…Secured Trust-aware Routing Protocol for Low-Power and Lossy Networks (SecTrust-RPL) in the IoT determines and detaches routing attacks by offering improved network performance (Airehrour, et al, 2019). Secure routing protocols, like Expected Forwarded Counter (EFW) (Paris, et al, 2013), Semi-Distributed Reputationbased Intrusion Detection System (S-D RepIDS) (Trivedi, et al, 2010), Trusted based routing using Dominating Set Approach (TRDSA) (Kukreja & Reddy, 2012), Secure Resilient Reputation-based Routing (SR3) (Altisen, et al, 2013), reputation-based Framework for Sensor Networks (RFSN) (Ganeriwal, et al, 2008), and Ad Hoc On-Demand Distance Vector Reputation Extension (AODV) (Over MANET, 2012)are illustrated. Secure Resilient Reputation-based Routing (SR3), Expected Forwarded Counter (EFW), and Trusted based routing using Dominating Set Approach (TRDSA) use reputation methods for core deductive components (Hatzivasilis, et al, 2017).…”
Section: Chaotic Whale Crow Optimization Algorithm For Secure Routing...mentioning
confidence: 99%
“…Moreover, Bayrakdar [19] suggested a cooperative communication‐based access approach for WSNs to improve network throughput and energy efficiency. Kukreja et al [20] suggested a new trust‐based routing scheme named TRDSA by incorporating a dominating set mechanism. This approach aims to achieve secure ad hoc routing in wireless networks.…”
Section: Introductionmentioning
confidence: 99%
“…temperature). In the Trusted based Routing using Dominating Set Approach (TRDSA) [107] only a set of trusted nodes with sufficient remaining energy need to operate in promiscuous mode and capture malicious activity, reducing the overall energy consumption. Expected Forwarded Counter (EFW) [108] combines cross network-layer observations.…”
Section: Hardware Versus Software Implementationsmentioning
confidence: 99%
“…To address the above issue, routing protocols are designed that integrate the energy consumption data in the path selection process [107]. The nodes exchange their remaining energy level.…”
Section: 4 4 Energy Metric Energy Metric Energy Metricmentioning
confidence: 99%
See 1 more Smart Citation